Evaluasi Kapasitas Genset Sebagai Sistem Back-Up Energi Listrik di Gedung Sekretariat Daerah - Zuroida, Afidah; Galuh Prawestri Citra Handani; Hanifiyah Darna Fidya Amaral; Rohmanita Duanaputri; Bayu Prasetyo (Elposys: Jurnal Sistem Kelistrikan, 2025)
Generator sets (gensets) are important tools to be available in public places as a backup source of electrical power, if there is a power outage from the main electrical source. In this study, an evaluation analysis of the generator capacity was carried out in the West Kalimantan secretariat building on April 2023. This building has a total load of 677 kW supplied by PLN medium voltage 20 kV and lowered by a 630 kVA step-down transformer. Current observations were made during Off Peak Load Time at 13.00-15.00 and Peak Load Time at 17.00-19.00. From this experiment, it can be concluded that in April 2023 the highest peak load usage was 568.67 kW or 710.83 kVA. After the calculations have been done, the generator power capacity in the building must be 651.61 kW, while the generators used were two units with a power capacity of 1280 kW. Thus, the generator has met the electrical energy needs of the building. The efficiency of the generator when the genset works for 60 minutes in the building is still relatively low, which is 26.25%. The ACB safety rating used on the outgoing genset to the Low Voltage Main Distribution Panel (LVMDP) has a rating of 2000 A for one genset unit and 4000 A for two synchronous genset units, which is in accordance with the calculation of the safety capability value from PUIL 2011 reference.